Optimization Of Development With The People Centered Development Model Through Utilization Of Human Capital - Edy Suprayitno; Prof. Dr. V. Rudy Handoko, MS; Prof Dr. Arif Darmawan, SU (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
One of the important aspects in the implementation of good governance (Good Governance) is the opening of opportunities for the community to participate in making development decisions, including aspects of planning. The space prepared for community participation in the development planning process is the Development Planning Meeting (musrenbang) which is carried out in stages starting from the village, sub-district, district, province to the national level. Musrenbang activities are not only a forum for preparing activity plans to be implemented. The problems in this study are (1) How is the planning, implementation and evaluation of regional development in Sumenep Regency? (2) What is the people centered development model in regional development planning in Sumenep Regency? (3) How is the use of human capital in regional development planning in Sumenep Regency? In this study the approach taken was through a qualitative approach with a qualitative descriptive model (quasi-qualitative). Due to qualitative research, the philosophical foundation uses a phenomenological approach. This study used data collection techniques which included in-depth interviews, observation, and documentation. While the data analysis used qualitative analysis to build hypotheses. The research results obtained are (1) In the context of planning, implementing and evaluating regional development in Sumenep Regency, it's just that supervision is still not running optimally (2) In the context of the people centered development model in regional development planning in Sumenep Regency, development planning has been carried out quite well, (3) In the context of utilizing human capital in regional development planning in Sumenep Regency, the context of community capabilities has begun to be able to balance government officials in implementing development planning, community education has a significant influence on efforts to support development planning and implementation in Sumenep.